2017
DOI: 10.1136/bmjsem-2016-000213
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time physical activity and quality of life in medical students: results from a multicentre study

Abstract: Background/aimWe evaluated the association between leisure time physical activity (PA) and quality of life (QoL) in medical students. Our hypothesis was that there was a positive association between volume of PA and various domains of perception of QoL.MethodsData were evaluated from a random sample of 1350 medical students from 22 Brazilian medical schools. Information from participants included the WHO Quality of Life questionnaire-short form (WHOQOL-BREF), a questionnaire specifically designed to evaluate Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
25

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 34 publications
5
54
0
25
Order By: Relevance
“…Our study suggests that private life (i.e., social ties and leisure activities) could be an important resource for handling study demands. These findings are in line with the results of earlier studies showing that social support and regular exercise are associated with lower psychological distress or rather better quality of life among medical students [35,38,45]. A New Zealand study showed that 'medical friendships' are helpful in adjusting to medical school due to emotional support and/or a shared understanding of academic structures [46].…”
Section: Effects Of Private Life On Studiessupporting
confidence: 90%
“…Our study suggests that private life (i.e., social ties and leisure activities) could be an important resource for handling study demands. These findings are in line with the results of earlier studies showing that social support and regular exercise are associated with lower psychological distress or rather better quality of life among medical students [35,38,45]. A New Zealand study showed that 'medical friendships' are helpful in adjusting to medical school due to emotional support and/or a shared understanding of academic structures [46].…”
Section: Effects Of Private Life On Studiessupporting
confidence: 90%
“…It is no surprise that, according to the results of our study, the degree of exercise had a positive impact on the GH dimension. The evidence of this can also be found in previous studies [32,33]. Among those studies are some systematic reviews and meta-analyses, in which enhanced HRQOL was demonstrated to have links with physical activities [34,35].…”
Section: Discussionsupporting
confidence: 61%
“…In addition to PA is a good way for the person to improve his physical, psychological and emotional health [9] and positively influences the personal perception of QoL and well-being [10,11]. QoL is a multidimensional construct, including psychological, physical, social and environmental domains [12]. There are four basic environments in which individuals can be physically active.…”
Section: Introductionmentioning
confidence: 99%